Tuberculosis of the future (Faculty of Medicine Universitas Indonesia, 2002)
Beginning and during the 20th century there were several milestones in TB control, including the development of vaccine and chemotherapy. But, as we enter the 21th century, TB continue be a global public health problem and if there is no improvement in TB control, the number of new TB cases is projected to rise to 11 million by 2020. Problems faced include inability to deliver / assure chemotherapy, deficient case finding, inadequate vaccine, rising level of drug resistance, failure to employ preventive chemotherapy and migration, HIV epidemics and nosocomial transmission. As far as recent advances in TB diagnostics, there is a need to find a tool for identification of latent infection, detection of diseases in migrant and other high risk populations, replace or facilitate AFB microscopy, improve the diagnosis of AFB smear-negative cases, and simple tools for determining drugs susceptibility. New diagnostic technologies includes nucleic acid probes, amplification tests, high performances liquid chromatography (HPLC), gas / liquid chromatography (GLC), and automated system for radiometric and non radiometric detection and molecular fingerprinting approach. In the coming years new drugs are needed, especially to shorten the duration of TB treatment or otherwise simplify its completion, improve the treatment of latent TB infection and to be eliminate. MDR-TB. There are some problems in pursue tuberculosis research because of the high investment required to bring a product to market and lack of likely commercial returns. Some new drugs and molecules with promising antimycobacterial activity include Fluoroquinolone, Oxazolidinones, Nitroimidazole, Thiolactomycine, Nitroimidazopyran and Isocitrate lyase inhibitor. To deliver good case finding and treatment, effective TB control program should be implemented in the country, as well as globally. The integration of TB control program with tobacco control program and chronic respiratory diseases control program could be one of the alternative. (Med J Indones 2002; 11: 190-4) Keywords: tuberculosis, future and recent advances